2021
DOI: 10.21037/apm-20-1208
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of resuscitation in cancer patients at the end of life—a population-based observational study from Germany

Abstract: Background: Cardiopulmonary resuscitation (CPR) is a medical emergency intervention aimed at ending a life-threatening cardiovascular arrest as quickly as possible. However, the medical ethics of starting CPR in patients who have incurable and terminal disease is a matter of controversy. This ethical dilemma affects cancer patients in particular, as they are often suffering from advanced disease in a palliative situation. Few data are as yet available concerning the prevalence of CPR in patients with terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…13,30 Third, the indicators we chose might be viewed as subjective; however, very similar parameters were found to be associated with poor outcomes when used in the assessment of ICU admission for hematologic malignancy. [31][32][33] Fourth, due to the retrospective nature, an indicator such as last cancer intervention to CPR may have limited utility, because clinicians likely will not know precisely when CPR will occur. Finally, we were unable to collect neurologic outcomes in our study.…”
Section: Discussionmentioning
confidence: 99%
“…13,30 Third, the indicators we chose might be viewed as subjective; however, very similar parameters were found to be associated with poor outcomes when used in the assessment of ICU admission for hematologic malignancy. [31][32][33] Fourth, due to the retrospective nature, an indicator such as last cancer intervention to CPR may have limited utility, because clinicians likely will not know precisely when CPR will occur. Finally, we were unable to collect neurologic outcomes in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of cardiac arrest among patients with cancer found that resuscitated patients with palliative care are younger than patients with cancer without palliative care, which could be another factor to explain the age difference. 22 It should be stressed that only OHCA cases with initiated CPR are included in this study.…”
Section: Discussionmentioning
confidence: 99%